Finite element modelling of a pattern of temperature distribution during travelling heat source from oxyacetylene flame - Alkali, A.U. (EDP Sciences, 2014)
A 3D Finite element model was developed to analyse the conduction temperature distribution on type 304 stainless steel workpiece. An experimental heating-only test was conducted using the input parameters from FEM model which predicted the temperature field on the 304 stainless steel work pieces. Similar temperature pattern was noticed for both the FEM model as well as the experimental. Conduction was observed to be the dominant heat transfer mode. Maximum temperatures were observed to occur at the regions of contact between flame heat and the work pieces. Maximum temperature attained during the two investigated runs was 355Â°C. Even so austenite crystal morphology was retained on the preheated workpiece. Â© 2014 Owned by the authors, published by EDP Sciences.